Development of Handouts on Redox Material to Improve the Students Cognitive Abilities Using the Sorogan-Bandongan Learning Model - Nur Ainun; Rinaningsih Rinaningsih (Jurnal Pijar MIPA, 2026)
The Sorogan-Bandongan learning model is a traditional approach to enhancing students’ cognitive abilities through a structured series of activities, including diagnostic testing, independent practice, and self-reflection. This model effectively bridges student-centered individual learning (Sorogan) with collective discussion and evaluation (Bandongan), fostering both personal responsibility and collaborative engagement. This Research and Development (R&D) study, employing Thiagrajan's 4D model (Define, Design, Develop, Disseminate) through the development stage, aims to evaluate the feasibility of a chemistry handout on redox reactions based on this model. The feasibility was assessed through three main criteria: validity, practicality, and effectiveness. Analysis of the research instruments revealed that the handout is highly qualified across all parameters. In terms of validity, both content and construct aspects received a mode score of 4, placing them in the "highly valid" category. Regarding practicality, the handout earned a 94.11% student response rate, while direct observations of student activities across three sessions yielded consistently high scores between 96.67% and 97.78%, categorizing it as "very practical." Finally, the effectiveness of the handout was demonstrated by a significant improvement in student learning outcomes. The analysis of pretest and posttest results showed an average N-Gain Score of 0.77, which falls into the "high" category, with a class mastery rate of 100%. These results confirm that integrating the Sorogan-Bandongan learning model into chemistry handouts is a highly effective and feasible strategy for improving students’ cognitive understanding of redox material.